Análisis a los estados financieros del Gobierno Autónomo Descentralizado del Cantón Zamora, periodos 2021-2022 - Vasquez Toledo, Jhosef Humberto (2024)
Effective decision-making in public entities depends largely on the quality of the financial information available. Analysis of financial statements is a fundamental tool to generate this information and understand the financial situation of an entity. However, determining the optimal financial structure is a complex challenge, influenced by various internal and external factors. This research aims to carry out the financial analysis of the Municipality of the Zamora Canton using a mixed approach (qualitative and quantitative). Using deductive and comparative methods, an analysis was applied to the financial statements provided by the entity, in order to determine its financial structure during the period studied and compare it with the established theoretical frameworks. From the results obtained, it was evident that the Municipality of the Zamora Canton has a relatively stable financial structure, with low debt and a high use of its own resources that finance its operations. However, some aspects worth highlighting are identified, such as the significant change in the Investments in Infrastructure Works account, the decrease in the efficiency of financing collection and the high dependence on income by the State. In conclusion, although the entity has a solid financial structure, there are works financed by results from previous years, estimates in a specific account that are too optimistic and a great dependence on state financing.